2013
DOI: 10.1590/s0102-86502013000300009
|View full text |Cite
|
Sign up to set email alerts
|

The ileum as a determinant organ of the functional liver cell mass in rats

Abstract: PURPOSE:To evaluate if the ileum resection changes the functioning liver cell mass, the hepatic metabolism and the biodistribution of radiopharmaceutical in rats. METHODS:Twelve Wistar rats weighing 285g±34g were randomly divided into the ileum resection group (n = 6) and sham group rats (n = 6). After 30 days, they were anesthetized and 0.1mL of 99m-Tc-phytate (0.66MBq) was injected via femoral vein. After 30 minutes, blood samples were collected for red blood cells radioactive labeling and serum ALT, AST and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Despite the colon resection was not performed in the present study, we intend to use this model in the near future in this research line. In other studies, impaired liver regeneration after bowel resection has been demonstrated [25][26][27][28] , confirming the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the colon resection was not performed in the present study, we intend to use this model in the near future in this research line. In other studies, impaired liver regeneration after bowel resection has been demonstrated [25][26][27][28] , confirming the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with our previous findings. We demonstrated that the ileum resection negatively influenced the liver regeneration, liver mass and liver function in the late postoperative period 35 .…”
Section: Discussionmentioning
confidence: 84%